Emergence of Nanotechnology as a Powerful Cavalry against Triple-Negative Breast Cancer (TNBC) - Chaudhuri A.; Kumar D.N.; Dehari D.; Singh S.; Kumar P.; Bolla P.K.; Kumar D.; Agrawal A.K. (My University, 2025)
Triplenegative breast cancer (TNBC) is considered one of the unmanageable types of breast cancer, involving devoid of estrogen, progesterone, and human epidermal growth factor receptor 2 (HER 2) receptors. Due to their ability of recurrence and metastasis, the management of TNBC remains a mainstay challenge, despite the advancements in cancer therapies. Conventional chemotherapy remains the only treatment regimen against TNBC and suffers several limitations such as low bioavailability, systemic toxicity, less targetability, and multidrug resistance. Although various targeted therapies have been introduced to manage the hardship of TNBC, they still experience certain limitations associated with the survival benefits. The current research thus aimed at developing and improving the strategies for effective therapy against TNBC. Such strategies involved the emergence of nanoparticles. Nanoparticles are designated as nanocavalries, loaded with various agents (drugs, genes, etc.) to battle the progression and metastasis of TNBC along with overcoming the limitations experienced by conventional chemotherapy and targeted therapy. This article documents the treatment regimens of TNBC along with their efficacy towards different subtypes of TNBC, and the various nanotechnologies employed to increase the therapeutic outcome of FDAapproved drug regimens. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.